Implementation of SINERGIS disc to increase knowledge of PROLANIS member in monitoring diabetes mellitus independently during COVID-19 pandemic - Abiyyu Naufal Susanto; Maryana Maryana; Titik Fajriyati Nur Khasanah; Wahyu Febriana; Joko Tigo Narimo Bekti (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Diabetes mellitus is a disease of blood sugar, protein, and fat metabolism disorders which is often referred to as "The Silent Killer" which means it works like termites, and slowly but damages vital organs. Community empowerment needs to be done considering the tendency to increase the incidence and prevalence of diabetes mellitus around the world. This study aims to see the effect of the Diabetes Mellitus Integrated Monitoring System (Sistem Monitoring Terintegrasi Kencing Manis/ SINERGIS) program on the level of knowledge in people with type 2 diabetes mellitus at Seyegan Public Health Center (PHC). This study used a randomized pretest-posttest control group design. The sample in this study was 40 respondents who were selected with the purposive sampling technique. The research took place at the Seyegan PHC, Sleman, Yogyakarta Special Region. The instrument used was the DKQ-24 (Diabetes Knowledge Questionnaire) questionnaire with 24 question items. The test was a paired t-test. There is a significant difference in the mean value of knowledge between the pretest (14.21) and posttest (19.84) with a difference of 5.63 with the statistical test results of p-value = 0.001 (p <0.05). From this research, it can be concluded that there is an effect of health education on diabetes mellitus using SINERGIS discs on the knowledge level of diabetes mellitus patients.